Tertiary education students’ learning experience during the COVID-19 outbreak - Tharani Sree Kondal Rao; Rajalakshmi Ganesan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Online learning is commonly used nowadays for several aspects as an advanced form of learning, through hi-tech gadgets. However, as convenient and efficient it sounds, some students find it difficult to cope with online learning. The goal of the current study is to answer the research questions of “What is experienced by students in an online learning environment?” and “Does online learning environment experience improve/hinders/maintains academic achievements?” via an Interpretative Phenomenological Analysis (IPA). 16 participants were interviewed and the data obtained were analyzed through the IPA, illustrated four superordinate themes which are, the dynamics of online learning, significance of lecturers in quality of online learning, effects of environment of online learning and effects on self, due to online learning. The impact of online learning during the COVID -19 pandemic have indeed impacted tertiary student’s perception of education, their mental health well-being and their academic performance. This highlights the need to develop ways to overcome this situation and ensure quality education can still be delivered and received.